Assessment of mitochondrial DNA as an indicator of islet quality: an example in Goto Kakizaki rats - Alán, L; Špaček, T; Zelenka, J; Tauber, J; Berková, Z; Zacharovová, K; Saudek, F; Ježek, P (Transplantation proceedings, 2011)
BACKGROUND: Diabetic Goto Kakizaki (GK) rats represent an established model of type 2 diabetes that exhibit an onset of pancreatic islet (PI) pathology characterized by islet hypertrophy with a decreased number of insulin-secreting β-cells. Among the remaining β-cells, oxidative phosphorylation (OXPHOS) and consequently glucose-stimulated insulin secretion (GSIS) are impaired, perhaps owing to a deficit in mitochondrial DNA (mtDNA). We sought to identify this abnormality. METHODS: β-Cells were obtained from Accutase-dissolved PI isolated from GK or Wistar rats and sorted based on the positive Zn(2+) signal of Newport Green. The mtDNA copy number per cell was quantified as the amplicon ratio by polymerase chain reaction using specific primers against the rat ND5 mt gene and UCP2 nuclear gene. RESULTS: The 12-month-old GK rats exhibited drastically reduced copy numbers per remaining β-cell, from 7,400 ± 600 in 12-month old Wistar rats (100%) to 24 ± 4%; mtDNA content in heart and liver was 70 ± 25% and 60 ± 20%, respectively. Versus age-paired Wistar rats, 6- and 4-month-old GK rats showed reductions to 60 ± 15% and 50 ± 20%, respectively. CONCLUSIONS: OXPHOS of remnant β-cells in diabetic GK was drastically impaired due to the lack of sufficient mtDNA levels. We suggest the use of mtDNA quantification to quickly assess PI quality before transplantation.
Keywords: Animals; experimentální diabetes mellitus; Langerhansovy ostrůvky; Rats, Wistar; DNA, Mitochondrial; Gene Dosage; Oxidative Phosphorylation; Islets of Langerhans; Oxygen Consumption; Zinc; Insulin; zinek; separace buněk; oxidativní fosforylace; modely nemocí na zvířatech; glukosa; Glucose; mitochondriální DNA; Disease Models, Animal; krysa rodu Rattus; Cell Separation; buněčné kultury; zvířata; Cell Culture Techniques; genová dávka; inzulin; Rats; spotřeba kyslíku; potkani Wistar; Diabetes Mellitus, Experimental